2007
DOI: 10.2527/jas.2007-0182
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal patterns in normal and hyperleptinemic mares in response to three common feeding-housing regimens1

Abstract: We previously reported that a rise in plasma leptin concentrations followed the rise in insulin and glucose in meal-fed horses, whereas horses maintained on pasture had little fluctuations in hormonal patterns. We have also described a hyperleptinemic-hyperinsulinemic condition that occurs in about 30% of our light horse mares of high body condition maintained on pasture. The present experiment was designed to 1) study the effect of 3 common feeding-housing regimens on leptin and other metabolic hormones in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Supplementary feeding increased the risk of hyperinsulinaemia by almost 5‐fold. Insulin concentrations have been shown to increase after feeding concentrates and remain elevated for 6–8 h . Although the ponies in this study had concentrates withheld on the morning of sampling, supplementary feeding of ponies with concentrate feed is likely to result in obesity and thus contribute to the development of IR, and many owners identified feeding of grain as a perceived risk factor for laminitis.…”
Section: Discussionmentioning
confidence: 81%
“…Supplementary feeding increased the risk of hyperinsulinaemia by almost 5‐fold. Insulin concentrations have been shown to increase after feeding concentrates and remain elevated for 6–8 h . Although the ponies in this study had concentrates withheld on the morning of sampling, supplementary feeding of ponies with concentrate feed is likely to result in obesity and thus contribute to the development of IR, and many owners identified feeding of grain as a perceived risk factor for laminitis.…”
Section: Discussionmentioning
confidence: 81%
“…However, the effect of reduced feed intake or lack thereof on prolactin secretion was directly tested by a second experiment described by Nadal et al [71], which revealed that total feed deprivation of mares for 72 hours did not alter prolactin concentrations in daily blood samples. Similarly, a feeding regimen of dried grass hay in a dry lot [73] did not alter prolactin concentrations in mares compared with when they were on pasture 24 hours per day (ad libitum grazing). For comparison, the dried hay-dry lot regimen reduced average insulin, leptin, and IGF-I concentrations dramatically compared with when mares were on ad libitum pasture.…”
Section: Feeding Effectsmentioning
confidence: 89%
“…However, not all studies confirm these findings (Gordon and McKeever, 2005), and daily fluctuations in leptin levels may be a consequence of the feeding schedule and/or feed composition. Leptin levels rise 8–10 h after a high carbohydrate (grain) meal and follow the rise in insulin levels (Steelman et al., 2007; Storer et al., 2007). In contrast, the observed peaks and troughs in insulin and leptin concentrations are blunted in horses receiving frequent meals, hay ad libitum or feeding on pasture (Storer et al., 2007).…”
Section: Introductionmentioning
confidence: 99%